2001
DOI: 10.1006/bbrc.2001.5622
|View full text |Cite
|
Sign up to set email alerts
|

Induction of SPARC by VEGF in Human Vascular Endothelial Cells

Abstract: SPARC/osteonectin/BM-40 is a matricellular protein that is thought to be involved in angiogenesis and endothelial barrier function. Previously, we have detected high levels of SPARC expression in endothelial cells (ECs) adjacent to carcinomas of kidney and tongue. Although SPARC-derived peptide showed an angiogenic effect, intact SPARC itself inhibited the mitogenic activity of vascular endothelial growth factor (VEGF) for ECs by the inhibiting phosphorylation of flt-1 (VEGF receptor 1) and subsequent ERK acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 30 publications
(21 reference statements)
4
44
0
1
Order By: Relevance
“…19 The exact role of SPARC in tumor angiogenesis is still unclear but may include a role in VEGF (vascular endothelial growth factor) functions and in extravasation of tumors cells mediated by increased permeability of the endothelial barrier. 17 SPARC overexpression has previously been associated with human tumors. 20 Porte et al 21 identified an association of SPARC with colorectal carcinoma, where neoplastic progression was associated with overexpression of the stromelysin-3 and SPARC genes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…19 The exact role of SPARC in tumor angiogenesis is still unclear but may include a role in VEGF (vascular endothelial growth factor) functions and in extravasation of tumors cells mediated by increased permeability of the endothelial barrier. 17 SPARC overexpression has previously been associated with human tumors. 20 Porte et al 21 identified an association of SPARC with colorectal carcinoma, where neoplastic progression was associated with overexpression of the stromelysin-3 and SPARC genes.…”
Section: Discussionmentioning
confidence: 97%
“…15,16 SPARC increases the production of collagenase, stromelysin, gelatinase, fibronectin and laminin in fibroblasts. 17 This causes degradation of both interstitial and basement membrane matrices 18 and increases endothelial permeability with the appearance of intercellular gaps, which provide a pathway for extravasation of tumor cells. 19 The exact role of SPARC in tumor angiogenesis is still unclear but may include a role in VEGF (vascular endothelial growth factor) functions and in extravasation of tumors cells mediated by increased permeability of the endothelial barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of Conditioned Medium (CM) for Zymography-Proteins in CM were precipitated with 3 volumes of ethanol for at least 3 h at Ϫ80°C and collected by centrifugation at 15,000 ϫ g for 30 min at 4°C (29). After drying at room temperature, the precipitates were dissolved in PBS or mixed directly with SDS sample buffer (0.5 mM Tris-HCl (pH 6.8), 1% SDS, 0.2% glycerol).…”
Section: Methodsmentioning
confidence: 99%
“…1 J ). Kupprion et al 52 have shown that SPARC inhibits the mitogenic effect of VEGF in microvascular endothelial cells, and there are multiple interactions between SPARC and VEGF signaling; 53,54 SPARC is induced by VEGF in vascular endothelial cells 55 and affects wound healing in a cell type-specific fashion. 56 Treatment of SuHx rats with the VEGFR3 inhibitor MAZ51 ameliorates the severity of pulmonary hypertension and partially prevents lumen obliteration Treatment of SuHx rats with every-other-day dosing of MAZ51 reduced right ventricular systolic pressure (RVSP) without affecting RV hypertrophy (Fig.…”
Section: Survey Of Expressed Vegf Isoforms and Vegf Receptors In Lungmentioning
confidence: 99%